2021
DOI: 10.1109/tgrs.2020.3002945
|View full text |Cite
|
Sign up to set email alerts
|

Single-Look Multi-Master SAR Tomography: An Introduction

Abstract: This article addresses the general problem of single-look multi-master SAR tomography. For this purpose, we establish the single-look multi-master data model, analyze its implications for the single and double scatterers, and propose a generic inversion framework. The core of this framework is the nonconvex sparse recovery, for which we develop two algorithms: one extends the conventional nonlinear least squares (NLS) to the single-look multi-master data model and the other is based on bi-convex relaxation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Under this assumption, we establish a linear mapping relationship between the multiaspect SAR amplitude images and a real-valued 4D (spatial location (x, y, z) and radar azimuth angle θ) scattered field of the target. The image formation model deduced in this section is inspired by those used in incoherent tomography techniques [32] and multimaster SAR tomography techniques [33,34], while the neural network in the next section is used to solve the inverse problem of this image formation model.…”
Section: Sar Amplitude Image Formation Modelmentioning
confidence: 99%
“…Under this assumption, we establish a linear mapping relationship between the multiaspect SAR amplitude images and a real-valued 4D (spatial location (x, y, z) and radar azimuth angle θ) scattered field of the target. The image formation model deduced in this section is inspired by those used in incoherent tomography techniques [32] and multimaster SAR tomography techniques [33,34], while the neural network in the next section is used to solve the inverse problem of this image formation model.…”
Section: Sar Amplitude Image Formation Modelmentioning
confidence: 99%
“…As discussed earlier, the SM signal model with a fixed master image is limited in long-baseline cases. Previous research [39,40,42,43] has proposed a bistatic-like MM signal model for atmospheric phase error elimination, which can be adopted for image pairing in D-TomoSAR. This model allows for an unfixed master image.…”
Section: Signal Modelmentioning
confidence: 99%
“…To address this issue, we propose a solution through the idea of MM D-TomoSAR using a non-fixed master image. Although the bistatic-like MM model has been introduced previously in [39,40,42,43], it is a limited one, and only bistatic-like SAR images can be paired to generate interferograms to avoid atmospheric phase errors. In contrast, the proposed model effectively utilizes the advantage that UAV-SAR is free from atmospheric phase errors.…”
mentioning
confidence: 99%
“…Spectral estimation based conventional TomoSAR inversion algorithms, however, require complex spectral samples at several wavenumbers, phase-normalized to a single master phase. In a current parallel work by one of the authors [28] it is shown that pixel-wise TomoSAR using multi-master acquisitions is a non-convex hard to solve problem. This is true for pixel-wise tomographic inversion or for point scatterers.…”
Section: Non-local Tomosar For Multi-master Insarmentioning
confidence: 99%